British fishery research in the Barents Sea - Lee, Arthur (Polar Record, 1956)
Since January 1949 the Arctic Team of the Fisheries Laboratory, Lowestoft, has been carrying out fishery research from the Ministry of Agriculture, Fisheries and Food Research vessel Ernest Holt , an Arctic-type trawler specially built and fitted out so that hydrographic and biological observations can be made on the Arctic fishing grounds throughout the year. At the time of writing the naturalists in the Arctic Team consist of Michael Graham (Leader); G. C. Trout and R. J. H. Beverton (Population studies); J. Corlett and P. T. Marshall (Plankton); Arthur Lee and H. W. Hill (Hydrography); R. W. Blacker (Benthos). I wish to thank my colleagues for allowing me to draw freely on their work which is in preparation for publication, and for contributing the illustrations to this article.